Seismogenic Zone Structures Revealed by Improved 3‐D Seismic Images in the Nankai Trough off Kumano. (10th May 2019) - Shiraishi, Kazuya; Moore, Gregory F.; Yamada, Yasuhiro; Kinoshita, Masataka; Sanada, Yoshinori; Kimura, Gaku
Abstract: To reveal the detailed deformation structures related to plate subduction in the Nankai Trough, we applied up‐to‐date technologies to improve our 3‐D seismic images. This region is dominated by a megasplay fault system that consists of a coseismic out‐of‐sequence thrust branching from the plate interface and separating the inner and outer accretionary prism. The 3‐D seismic volume was acquired off Kumano in 2006 as a preliminary site survey as part of the Nankai Trough Seismogenic Zone Experiment. The preprocessed data quality was improved by recovering the broadband responses and by better attenuating multiple reflections and noise. New reflection images were then produced using prestack time migration and prestack depth migration with updated velocity models. The new velocity model suggests the possible existence of a high‐velocity zone just above the megasplay fault, which might indicate petrophysical alteration in the seismogenic zone. The fault geometry with spatial dip angle variation and the overburden velocities are important factors for further estimating the force distribution along the coseismic fault. Deformation structures newly imaged beneath the Kumano Basin and dipping layers above the megasplay fault imply complex thrusting and possible fluid flow paths within the inner prism. Fine‐scale deformation features are clarified in the shallow areas from the outer prism to the transition zone, which are useful for reconstructing the accretionary prism development. A low‐reflectivity zone, including an isolated layered block, may be originally underthrusted sediments that have been remobilized during later strike‐slip faults along the edge of Kumano Basin. Plain Language Summary: Deformed sediments that have been stripped off the subducting plate and added to a growing mass of accreted sediments in the Nankai Trough, off the coast of southwest Japan, are cut by a major active thrust fault that is considered to be the potential primary location of periodic great earthquakes that generate destructive tsunamis. To reveal the complex geological structures around the fault, we improved seismic reflection profiles by reprocessing legacy 3‐D seismic data using the latest signal processing technologies. The improved profiles show a thick high‐velocity zone that may potentially indicate hardening of rocks due to mineral precipitation and subsequent filling of fractures above the fault. We also better imaged deformation structures that were generated during the past multiple faulting events in the plate subduction process. Key Points: Seismic reflection imaging in the Nankai Trough off Kumano has been improved by applying recent data processing technologies A high‐velocity zone identified above the megasplay fault may indicate petrophysical alteration at the depth of the seismogenic zone Complex thrust structures and possible fluid flow paths in the accretionary prism are inferred from the new depth images